Perancangan Pengalaman Pengguna Aplikasi Percetakan PT Ajitama berbasis Mobile dengan Metode Design Thinking - Fariz Sokhinda Hamza; Herman Tolle; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Today, the printing industry is one of the ways to carry out marketing and promotion of a product. One of them is PT Ajitama. It is a company that focuses on the printing industry. The products produced by the company are banners, posters, paper bags, and others. Right now, the media that the company uses to provide their services order is through email, and this media is seen as ineffective and inefficient. This study aims to facilitate the customers in making their order and performing their transaction at PT Ajitama. The method used in this study is design thinking. Design thinking is a method that focuses on user experiences, and it consists of some stages, namely, empathizes, defines, ideates, prototype, and test. On the testing of usability, there are 10 participants from 2 categories, namely, the people who have used PT Ajitama services, and the probable customers, and among them, there is 1 category of combined data between the 2 categories mentioned previously. From the three aspects tested, they are averaged and resulted in the final score of usability. The final score of usability obtained from the category of the people who have used the service is 80,7, hence it is categorized as A (Excellent).